Range distribution of the mountain nyala (Tragelaphus buxtoni) in Ethiopia - Evangelista, Paul (Colorado State University. Libraries, 2008)
The use of statistical models to predict species distributions and suitable habitat has become an essential tool for wildlife management and conservation planning. Models have been especially useful with rare and endangered wildlife species. One such species is the mountain nyala (Tragelaphus buxtoni), a spiral-horned antelope endemic to the Ethiopian highlands. The full range of the species has never been adequately defined and recent discoveries of new populations suggest that others may exist undetected. To identify potential mountain nyala occurrences, we used classification tree analysis to predict suitable habitat using 76 climatic, topographical and vegetative variables. Three model evaluation methods showed a strong performance of the final model with an overall accuracy of 90%, Cohen's maximised κ of 0.80 and area under the receiver operating characteristic curve (AUC) value of 0.89. Minimum temperature and maximum precipitation generally had the greatest predictive contributions to suitable mountain nyala habitat. The predicted habitat covered an area of 39378 km2, with the majority occurring in remote forests on the southern escarpment of the Bale Mountains. Other areas within the predicted range may be too impacted by human and livestock populations to support mountain nyala; however, the model will be useful in directing future surveys for new populations while offering clues to the species historical range.
Natural Resource Ecology Laboratory (NREL)
Ethiopia Project
Keywords: wildlife; species distribution model